2018
DOI: 10.1128/aac.01252-18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pregnancy on the Pharmacokinetic Interaction between Efavirenz and Lumefantrine in HIV-Malaria Coinfection

Abstract: Artemether-lumefantrine is often coadministered with efavirenz-based antiretroviral therapy for malaria treatment in HIV-infected women during pregnancy. Previous studies showed changes in lumefantrine pharmacokinetics due to interaction with efavirenz in nonpregnant adults. The influence of pregnancy on this interaction has not been reported. This pharmacokinetic study involved 35 pregnant and 34 nonpregnant HIV-malaria-coinfected women receiving efavirenz-based antiretroviral therapy and was conducted in fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…Six studies published following this meta‐analysis were identified 15–20 . Out of these, five were inconclusive regarding need for dose adjustments but rather commented that the clinical relevance of statistically significant differences in pharmacokinetic parameters warrants further evaluation.…”
Section: Findings From Review Of Pharmacokinetic Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Six studies published following this meta‐analysis were identified 15–20 . Out of these, five were inconclusive regarding need for dose adjustments but rather commented that the clinical relevance of statistically significant differences in pharmacokinetic parameters warrants further evaluation.…”
Section: Findings From Review Of Pharmacokinetic Literaturementioning
confidence: 99%
“…Six studies published following this meta-analysis were identified. [15][16][17][18][19][20] Out of these, five were inconclusive regarding need for dose adjustments but rather commented that the clinical relevance of statistically significant differences in pharmacokinetic parameters warrants further evaluation. All the studies used day-7 lumefantrine concentrations of either >175 ng/mL or >280 ng/mL as a proxy for adequate dosing to avoid treatment failure, based on the demonstrated correlation between concentrations below these targets and risk of recrudescent malaria.…”
Section: Antimalarial Drugsmentioning
confidence: 99%
“…Adegbola et al examined the DDI between the antiretroviral EFV and the antimalarial LF in pregnant women compared to women postpartum [72]. Lumefantrine is primarily metabolized by CYP3A4 and EFV induces CYP3A4 activity, resulting in a decreased LF exposure in non-pregnant patients as showed in Fig.…”
Section: Efavirenz and Lumefantrinementioning
confidence: 99%
“…Lumefantrine is primarily metabolized by CYP3A4 and EFV induces CYP3A4 activity, resulting in a decreased LF exposure in non-pregnant patients as showed in Fig. 2a [72,73]. Pregnant women treated with LF have ~ 30% lower LF concentrations at day 7, a marker for therapeutic efficacy, compared with nonpregnant women [74][75][76][77].…”
Section: Efavirenz and Lumefantrinementioning
confidence: 99%
“…[22][23][24][25][26][27] Despite the wide-spread use of AL, no reports to our knowledge have addressed the effects of efavirenz-based ART on AL pharmacokinetics in HIV-infected pregnant women; previous studies have only investigated the effects of pregnancy on this treatment combination. 28 Our goal is to inform specific artemether-lumefantrine dosing guidelines for efavirenz-treated HIV-infected pregnant women.…”
Section: Introductionmentioning
confidence: 99%